Hematopoietic stem/progenitor involvement in retinal microvascular repair during diabetes: Implications for bone marrow rejuvenation. (October 2017) - Bhatwadekar, Ashay D.; Duan, Yaqian; Korah, Maria; Thinschmidt, Jeffrey S.; Hu, Ping; Leley, Sameer P.; Caballero, Sergio; Shaw, Lynn; Busik, Julia; Grant, Maria B.
Abstract: The widespread nature of diabetes affects all organ systems of an individual including the bone marrow. Long-term damage to the cellular and extracellular components of the bone marrow leads to a rapid decline in the bone marrow-hematopoietic stem/progenitor cells (HS/PCs) compartment. This review will highlight the importance of bone marrow microenvironment in maintaining bone marrow HS/PC populations and the contribution of these key populations in microvascular repair during the natural history of diabetes. The autonomic nervous system can initiate and propagate bone marrow dysfunction in diabetes. Systemic pharmacological strategies designed to protect the bone marrow-HS/PC population from diabetes induced-oxidative stress and advanced glycation end product accumulation represent a new approach to target diabetic retinopathy progression. Protecting HS/PCs ensures their participation in vascular repair and reduces the risk of vasogdegeneration occurring in the retina.